2004
DOI: 10.1002/cbic.200300817
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Putative Agonist‐Binding Modes in the Human A1 Adenosine Receptor

Abstract: A recent study reported a model of the human A(1) adenosine receptor and its agonist binding site, proposing two putative binding modes in the same binding site for the natural agonist, adenosine. The present work investigates the flexibility of this binding site by exhaustive exploration with the natural agonist and with three other adenosine derivatives: N6-cyclopentyladenosine (CPA), 2-chloro-N6-cyclopentyladenosine (CCPA), and 5'-N-ethylcarboxamidoadenosine (NECA). Our aim was to find a common binding mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…(1) is just a constant that cannot be concerned with the relative translational and rotational entropic terms to binding and that such contributions must be parameterized into the α parameter. Alternative, these authors have demonstrated that the α parameter is given by the slopes of the linear relationship found in water and receptors, between the ΔΔG nonpolar or <V vdw l‐s > energies and the number of heavy atoms for 25 different ligands,15, 16, 18, 22, 23, 51 while the γ correction term is related to their intercepts at zero ligand size 5, 6, 45…”
Section: Resultsmentioning
confidence: 99%
“…(1) is just a constant that cannot be concerned with the relative translational and rotational entropic terms to binding and that such contributions must be parameterized into the α parameter. Alternative, these authors have demonstrated that the α parameter is given by the slopes of the linear relationship found in water and receptors, between the ΔΔG nonpolar or <V vdw l‐s > energies and the number of heavy atoms for 25 different ligands,15, 16, 18, 22, 23, 51 while the γ correction term is related to their intercepts at zero ligand size 5, 6, 45…”
Section: Resultsmentioning
confidence: 99%
“…Using fixed values for and , while optimizing , not only provided the best absolute binding free energies for the ligands but also showed that the coefficients of the LIE method are independent of the force field used and that only might need to be optimized to account for the hydrophobicity of the active site. Gutierrez-de-Teran et al 157 used a two-step approach to analyze the binding modes of different agonists on human A 1 adenosine receptor (hA 1 AR). The natural agonist adenosine and three synthetic derivatives were docked onto a theoretical model of hA 1 AR.…”
Section: B Linear Interaction Energy Methodsmentioning
confidence: 99%
“…In particular, Gutiérrez-de-Terán and coworkers applied it with the aim of discriminating among two different binding modes of agonists of the adenosine A 1 receptor generated by automatic docking [60]. More recently, we applied the LIE method to the calculation of the activity of a series of antagonists of the P2Y 1 receptor [7].…”
Section: Structure-based Methodologiesmentioning
confidence: 99%